2006
DOI: 10.1634/stemcells.2006-0309
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Large‐Scale Generation of Human Platelets from Cord Blood CD34 + Cells

Abstract: In the present investigation, we generated platelets (PLTs) from cord blood (CB) CD34؉ cells using a three-phase culture system. We first cultured 500 CB CD34

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 43 publications
5
114
0
Order By: Relevance
“…1 Numerous investigators have tried to increase CB stem cell numbers by culturing CD34 ϩ cells ex vivo under a variety of culture conditions; these attempts have, however, met with limited success. [2][3][4][5][6][7][8][9][10][11][12][13] CBHSCs/HPCs have also been used to generate alternative sources of terminally differentiated blood cells for use as transfusion products. 4,8 Adult blood HSCs/HPCs, human embryonic stem cells (ES) as well as induced pluripotent stem cells (iPS) have also been used for this same purpose.…”
Section: Introductionmentioning
confidence: 99%
“…1 Numerous investigators have tried to increase CB stem cell numbers by culturing CD34 ϩ cells ex vivo under a variety of culture conditions; these attempts have, however, met with limited success. [2][3][4][5][6][7][8][9][10][11][12][13] CBHSCs/HPCs have also been used to generate alternative sources of terminally differentiated blood cells for use as transfusion products. 4,8 Adult blood HSCs/HPCs, human embryonic stem cells (ES) as well as induced pluripotent stem cells (iPS) have also been used for this same purpose.…”
Section: Introductionmentioning
confidence: 99%
“…By employing this technique, the requirement for seeded MK progenitors can be reduced. To our knowledge, Matsunaga et al (2006) reported the highest yields of platelet per seeded HSC, generating 1.26-1.68 9 10 11 platelets from 5 9 10 6 HSCs (amount of CB-derived HSCs per donor).…”
Section: Low Efficiency Of Megakaryopoiesismentioning
confidence: 92%
“…PB-derived HSCs are preferable for generating platelets but the proliferation capacity is reduced once the cells are committed into megakaryopoiesis. Therefore, a multiphase culture system was proposed to allow successive goals: extensive HSC expansion, optimized MK maturation, and promotion of platelet formation (Matsunaga et al 2006;Panuganti et al 2013). Nevertheless, this strategy is applicable only to a single platelet production process.…”
Section: Low Hsc Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible to renovate the entire blood system transplanting hematopoietic stem cells (HSC) to allow a full recovery of the hematopoietic system in patients with different hematological disorders such as aplastic anemia and leukemia. This approach opened a wide range of clinical applications for progenitor blood cells transplantation including gene therapy (Zubler 2006) and the generation of specific mature cell types (Matsunaga et al 2006;Introna et al 2006).…”
Section: Introductionmentioning
confidence: 99%